2022
DOI: 10.18203/issn.2454-2156.intjscirep20221344
|View full text |Cite
|
Sign up to set email alerts
|

Assessing consumer use and behaviour patterns of oral nicotine pouches in a multi-country study

Abstract: <p class="abstract">Due to the novel nature of oral nicotine pouches, limited studies have been conducted on the usage of these products in real-world settings. Consumption patterns and use behaviour of current nicotine pouch users need to be investigated to monitor the use and support the assessment of reduced risk products. Here we report the findings of an online survey completed by 550 participants across Sweden, Denmark, Germany and Switzerland who were current nicotine pouch users. The key areas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For mRNA extraction, 5 × 10 5 cells were seeded into each well of 6-well plates and allowed to attach for 24 h. Cells were then exposed to diluted 20-min sample extracts for 4 h. The 20 min sample extracts were chosen as it is a common product use duration according to a survey by one product manufacturer (Prasad et al 2022 ). A 4 h exposure was used for gene expression experiments as it has been reported that gene expression of IL8 and IL6 have their peak after 4 to 8 h. Subsequently, mRNA was isolated using the NucleoSpin RNA, Mini kit for RNA purification (Macherey Nagel, Düren, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…For mRNA extraction, 5 × 10 5 cells were seeded into each well of 6-well plates and allowed to attach for 24 h. Cells were then exposed to diluted 20-min sample extracts for 4 h. The 20 min sample extracts were chosen as it is a common product use duration according to a survey by one product manufacturer (Prasad et al 2022 ). A 4 h exposure was used for gene expression experiments as it has been reported that gene expression of IL8 and IL6 have their peak after 4 to 8 h. Subsequently, mRNA was isolated using the NucleoSpin RNA, Mini kit for RNA purification (Macherey Nagel, Düren, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In three studies, the participants kept the products for 60 min in their oral cavities ( Lunell et al, 2020 ; Azzopardi et al, 2022b ; McEwan et al, 2022 ), which is three times the use duration compared with the presented study. A use duration of 20 min was chosen for two reasons: Firstly, a market survey conducted by a product manufacturer has revealed that the preferred duration for holding nicotine pouches in the oral cavity ranges from 5 to 20 min in Germany ( Prasad et al, 2022 ). The higher the nicotine strength of the pouch, the shorter was the preferred hold time ( Prasad et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A use duration of 20 min was chosen for two reasons: Firstly, a market survey conducted by a product manufacturer has revealed that the preferred duration for holding nicotine pouches in the oral cavity ranges from 5 to 20 min in Germany ( Prasad et al, 2022 ). The higher the nicotine strength of the pouch, the shorter was the preferred hold time ( Prasad et al, 2022 ). Secondly, as no clinical data for the use of pouches with high nicotine concentrations were available, it was unclear how participants would react to such a high nicotine dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the “worst-case scenario”, it was assumed that a person of 70 kg weight consumes 20 pouches per day. Both assumptions are based on previously published surveys (Havermans et al 2021 ; Prasad et al 2022 ). Since consumers are exposed to additives via serval exposure routes (e.g., food, cosmetics, and nicotine pouches), it was decided to calculate with 50% of the respective ADI value.…”
Section: Methodsmentioning
confidence: 99%